An Epistemic Programming Approach for Automated Nonmonotonic Reasoning Based on Default Logic - Goto, Yuichi; Ito, Takuya (2018 IEEE SmartWorld, Ubiquitous Intelligence and Computing, Advanced and Trusted Computing, Scalable Computing and Communications, Cloud and Big Data Computing, Internet of People and Smart City Innovation (SmartWorld SCALCOM UIC ATC CBDCom IOP SCI), 2018)
Epistemic programming was proposed as a novel program paradigm to program epistemic processes in scientific discovery, which regards conditionals as the subject of computing, takes primary epistemic operations as basic operations of computing, and regards epistemic processes as the subject of programming. On the other hand, any scientific discovery process may include nonmonotonic reasoning process because knowledge of any scientist is incomplete. However, there is no study about nonmonotonic reasoning under the epistemic programming paradigm. This paper presents an epistemic programming approach for automated nonmonotonic reasoning based on default logic as the first step to achieve automated nonmonotonic reasoning under epistemic programming paradigm.